Control of RAB7 activity and localization through the retromer‐TBC1D5 complex enables RAB7‐dependent mitophagy. (20th November 2017) - Jimenez‐Orgaz, Ana; Kvainickas, Arunas; Nägele, Heike; Denner, Justin; Eimer, Stefan; Dengjel, Jörn; Steinberg, Florian
Abstract: Retromer is an endosomal multi‐protein complex that organizes the endocytic recycling of a vast range of integral membrane proteins. Here, we establish an additional retromer function in controlling the activity and localization of the late endosomal small GTPase RAB7. Surprisingly, we found that RAB7 not only decorates late endosomes or lysosomes, but is also present on the endoplasmic reticulum, trans ‐Golgi network, and mitochondrial membranes, a localization that is maintained by retromer and the retromer‐associated RAB7‐specific GAP TBC1D5. In the absence of either TBC1D5 or retromer, RAB7 activity state and localization are no longer controlled and hyperactivated RAB7 expands over the entire lysosomal domain. This lysosomal accumulation of hyperactivated RAB7 results in a striking loss of RAB7 mobility and overall depletion of the inactive RAB7 pool on endomembranes. Functionally, we establish that this control of RAB7 activity is not required for the recycling of retromer‐dependent cargoes, but instead enables the correct sorting of the autophagy related transmembrane protein ATG9a and autophagosome formation around damaged mitochondria during Parkin‐mediated mitophagy. Synopsis: Restriction of RAB7 GTPase activity and localization to specific endomembrane domains depends on the RAB7 effector retromer, thus equipping it with a function in autophagosome formation that is independent of its canonical endocytic recycling role. The multiprotein RAB7 effector complex retromer regulates RAB7 activity and localization. Retromer interacts with the RAB7‐specific GTPase‐activating protein (GAP) TBC1D5. Loss of retromer or TBC1D5 results in depletion of inactive RAB7 pools and accumulation of hyperactivated RAB7‐GTP on endo‐lysosomes. Hyperactivated RAB7‐GTP loses its mobility within the cell. RAB7 accumulation on lysosomes disturbs ATG9a sorting and autophagosome formation during Parkin‐mediated mitophagy. Abstract : Restriction of RAB7 GTPase activity and localization to specific endomembrane domains depends on the RAB7 effector retromer, thus equipping it with a function in autophagosome formation that is independent of its canonical endocytic recycling role.